Drug-related crime and poverty in South Africa - Priviledge Cheteni; Gisele Mah; Yohane Khamfula Yohane (Cogent Economics & Finance, 2018)
This paper argues that the link between poverty and drug-related crime might be spurious. We take an empirical approach to investigate the causality and plausibility of this link. Firstly, we regress crime against envisaged explanatory variables in order to estimate the contribution of poverty to crime. Secondly, data is analysed using an ARDL ECM. The quarterly sample data for our estimation is for the period 1995-2016. We found a strong association between crime and poverty both in the short and long run. We recommend the government should focus on none income linked factors in dealing with the scourge of drug-related crime. As demonstrated in this study, various drug-related crimes are driven by socio-economic factors.
Keywords: D31; D63; D71; D81; 330; ARDL; drugs; Gini index; poverty headcount index; unemployment